Consensus, dissent and context in decision making on strategic issues at board meetings in family businesses - Teixeira, José Eduardo Valladares (2022)
Strategic issues have received continuous attention from management researchers in recent decades. The construct was applied in studies in several areas of strategic management, supported by multiple theoretical lenses. Although the literature points out that, in the organizational context, the individual interpretations of decision makers must be reconciled to generate shared understandings and meanings, preceding the response to strategic issues, most empirical studies on strategic issues have focused on individuals as a unit of analysis, emphasizing the CEO or the leader of a business unit. Less emphasis has been given in the literature to the study of the processes through which strategic issues are discussed and consensus on them reached in corporate governance bodies, such as boards of directors. This study aims to address this gap. Initially, I conducted a systematic review of the literature, in which I identified the current state of knowledge and lines of inquiry on strategic issues, pointed out gaps in this knowledge, and suggested opportunities for future research. Subsequently, given the scarcity of theoretical propositions and previous empirical results on the factors and processes affecting the interpretation and consensus on strategic issues in boards of directors, I carried out an exploratory, longitudinal, and qualitative study, based on the content of the board meeting minutes of a private family business group in Brazil, using a multi-level approach. This empirical investigation was the basis for proposing a process model for the interpretation and decision on strategic issues in a board of directors. The results of the literature review revealed important gaps in the knowledge about strategic issues. First, it confirmed that few studies have investigated the dynamic and temporal processes through which strategic issues are addressed by high-level teams. Second, it confirmed that more studies are needed to understand how individual interpretations of strategic issues are reconciled in collective understandings, leading to responses to strategic issues, in group and organizational contexts. And thirdly, the review pointed out that the methods used to study strategic issues must consider their cognitive and behavioral dimensions. The empirical study, in turn, was the basis for the development of a procedural model that integrates several concepts and answers several questions still open in the literature on strategic issues, in the context studied. The model identifies the processing stages and decisions taken by the board, both for the individual treatment of strategic issues and for the management of the organization's strategic agenda, and points to the factors that influence the achievement of consensus. The empirical study also contributed to clarify some aspects of strategic issues, on which conflicting positions are found in the academic literature, such as the importance of categorizing strategic issues for their processing in organizations, on the adoption of structured and formal methods for management of the strategic agenda and on the role, positive or negative, of cognitive conflict in the debate, construction of shared meaning and decision on strategic issues. Finally, the empirical study contributes to the understanding of the processing of strategic issues in a context little explored by the specialized literature, the advisory board of a family-owned private company, in a country with a culture with different characteristics from those observed in countries in which most studies on issues strategies are conducted. Given the exploratory nature of this study, however, more studies of a similar nature will be needed to support the generalization of its conclusions.